Effect of Nutrients and Plant Growth Regulators on Fruit Retention, Yield and Physico-Chemical Characteristics in Aonla Cv. NA-10 - S N Ghosh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2009)
To check pre-mature fruit drop in aonla cv. NA-10, an investigation was undertaken during 2007 and 2008 in a Seven year old private orchard at Jhargram, Paschim Midnapore, West Bengal, where the soil is red laterite and pH ranges between 4.5 and 5.5. Treatments included foliar spray of urea (0.2%) + DAP (0.2%), ZnSO4 (0.5%), Borax (0.4%), NAA (10 and 20 ppm), Vermiwash (3 ml/l), Humaur (2 ml/l) and water spray (control). Results of two years of investigation revealed that spray of NAA at 10 ppm was the best to increase fruit retention, followed by NAA 20 ppm, Vermiwash and Borax, which consequently resulted in the highest fruit yield of 54.9, 52.0, 46.8 and 36.2 kg/plant, respectively, against 13.8 kg in the control. Fruit weight was maximum with 0.5% ZnSO4 spray, followed by NAA 10 ppm. Fruit quality with regard to TSS, total sugar and ascorbic acid content was better in all the treated fruits compared to control.